Entrepreneurial Iatrogenesis: An explorative view - Montiel, Oscar; Canales-Garcia, Rosa Azalea; Gardea-Morales, Omar Humberto (European Journal of Family Business, 2023)
Focusing on different positions on the dark side of entrepreneurship (DSE) (Montiel & Clark, 2018; Shepherd, 2019), including the dark side of the family business (Montiel & Soto, 2021), we investigate iatrogenesis and its application in entrepreneurship. Through a literature review, we clarified and defined entrepreneurial iatrogenesis (EI) as a novel perspective, as well as the factors that can promote it. Through a conceptual model, a potential research stream is proposed, and the results show that both its elements and dimensions are related, a systemic position where the context has a determining action. We conclude that it is feasible to extend this analysis to the development of public policies focused on entrepreneurship, as well as the creation of entrepreneurship and small and medium-sized enterprise (SMEs) programs at different levels, such as government and universities, and in general for the entrepreneurial community to establish strategies that can foresee and address it.